Lipopolysaccharides and Prematurity: Effect on the Activity of Respiratory Chain Enzymes in Human Umbilical Venous Endothelial Cells - Neiße, Thomas; Janzen, Nils; Das, Anibh M. (Journal of Pediatric Biochemistry, 2015)
Fetal infection is associated with considerable perinatal morbidity. Dysfunction of human umbilical venous endothelial cells (HUVEC) may compromise fetal blood supply from the placenta. HUVECs were incubated with one of the key inflammatory mediators, lipopolysaccharides (LPS), and activities of respiratory chain enzymes were measured. Based on gestational age, HUVEC were divided into a mature and two premature groups from otherwise uncomplicated pregnancies (four patients each) and incubated for 1, 6, or 12 hours with LPS (100 ng/mL), respectively, incubation without LPS served as a control. We analyzed the activities of respiratory chain enzymes and citrate synthase as a mitochondrial marker spectrophotometrically. No significant differences in respiratory chain activities between the LPS-incubated cells and internal controls could be observed. However, we were able to demonstrate significant differences depending on gestational age: respiratory chain complex IV (p < 0.01) showed higher activity and complex I + III (p = 0.01) lower activity at lower gestational age. No such differences were observed for complex II + III, complex V, and citrate synthase. No effect on the activities of mitochondrial respiratory chain enzymes induced by LPS could be shown. Activity of complex I + III was decreased and activity of complex IV was increased at lower gestational age in control and LPS-incubated cells.
Keywords: lipopolysaccharide; HUVEC; preterm; energy metabolism; respiratory chain complex activity; umbilical cord cells